Adaptive digestive physiology in Southern African snakes - Dell, Bevan Keith (My University, 2017)
Snakes have often been proposed as ideal model organisms for studying digestive physiology. This is due to their easily–measureable and extreme changes in their digestive tracts in response to feeding, when compared to other vertebrates. Some species display extreme physiology regulation in response to feeding, a system known as digestive down-regulation. This regulation allows them to down-regulate their digestive tracts during their long fasting periods, which allows them to save energy. In response to feeding, they up-regulate their digestive tracts to a functional level, resulting in a significant increase in the size of the digestive organs during digestion. These changes have been found to be most noticeable in certain ambush foraging snakes. In contrast, actively foraging snakes appear to not display as extreme changes in response to feeding and keep their digestive tracts in a constant state of readiness. However it is not known if this pattern exists in all species and previous methods of classifying the digestive physiology have proven to be expensive, difficult and time consuming. My study aimed to investigate if museum specimens could be used as a cheap and quick method of classifying the characteristics of the digestive physiology within a species. I measured the dimensions of several organs from museum specimens from 13 species of southern African snakes, as well as recorded the relative size of the meal and month of capture. I compared measurements between postprandial and fasting individuals from each species as well as between individuals from each species with the same feeding state to assess whether they were able to down-regulate their digestive systems when not digesting. While the different foraging strategies appeared to be linked to differences in organ morphology, the presence of down-regulation was not clear-cut. No significant differences in organ size between feeding states were found within each species, and very few significant differences were found between species. Few correlations with organ size to meal size or seasonality were found. This suggests that the museum specimens are not suitable for determining digestive physiology in snakes, probably due to the poor quality of the specimens. I therefore recommend the use of freshly obtained samples as a suitable comparison rather than the use of museum specimens.
School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, 2017
Keywords: Snakes--Africa, Southern; Snakes--Physiology--Africa, Southern; Snakes--Digestive organs